1969
DOI: 10.1084/jem.129.6.1275
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancement of Bacterial Phagocytosis by Serum

Abstract: When Metchnikoff defined the process of phagocytosis in 1884 (1, 2), he conceded to serum the minor role of an dement that merely modified the phagocyte. However, in 1903 Wright and Douglas clearly established that phagocytosis of pathogenic bacteria could not occur without serum; that this effect was achieved by modification of the microorganism rather than the phagocyte; and that immunity developed in the serum, not the leukocyte (3, 4). Whether this serum effect was accomplished by specific antibody alone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Phagocytosis of pneumococci in the presence of type-specific opsonins and heat-labile factors has recently been reported by Johnston, Klemperer, Alper, and Rosen (23). These authors demonstrated that optimal phagocytosis of pneumococci requires 7S antibody, the first four components of complement, a heat-labile, dialyzable cofactor and a heat-labile, 5-6S, beta pseudoglobulin.…”
Section: Discussionmentioning
confidence: 95%
“…Phagocytosis of pneumococci in the presence of type-specific opsonins and heat-labile factors has recently been reported by Johnston, Klemperer, Alper, and Rosen (23). These authors demonstrated that optimal phagocytosis of pneumococci requires 7S antibody, the first four components of complement, a heat-labile, dialyzable cofactor and a heat-labile, 5-6S, beta pseudoglobulin.…”
Section: Discussionmentioning
confidence: 95%
“…IgM agglutinins in the presence of complement have been observed to form mixed aggregates (12), but red cells coated only with C3 did not adhere to monocytes. Cell-bound C3 may possess peptidase activity (23), which appears to be critical for the mediation of phagocytosis (24). It is possible that C3 enhances phagocytosis not because of a specific cellular receptor but rather because of the peptidase activity of activated C3.…”
Section: Resultsmentioning
confidence: 99%
“…This was interpreted as indicating that the interaction between activated C3 fragments and the target surface components was a very strong hydrophobic one. Another phenomenon, which was not addressed in a coherent manner, was the means by which C3b could bind to so wide a range of unrelated surfaces, including cell membranes Dalmasso & MullerEberhard, 1967), bacterial cell wall components (Johnston et al, 1969), immune aggregates (Theofilopoulos et al, 1974;Czop & Nussenzweig, 1976), zymosan (a large mannan complex from yeast cell walls) (Nicholson et al, 1974), and the artificial particle Sepharose (Goldstein et al, 1976). The key experiment, which provided the first evidence for the covalent binding of C3, was the analysis, by SDS-PAGE, of the membrane polypeptides of sheep erythrocytes after they had been treated sequentially with antibody, CI, C4, C2, and '251-labeled C3.…”
Section: Covalent Binding Of C3 and C4 To Targetsmentioning
confidence: 99%